2019
DOI: 10.5194/wes-2019-84
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel rotor blade fatigue test setup with elliptical biaxial resonant excitation

Abstract: Abstract. The full-scale fatigue test of rotor blades is an important and complex part of the development of new wind turbines. It is often done for certification according to the current IEC (2014) and DNV GL AS (2015) standards. Typically, a new blade design is tested by separate uniaxial fatigue tests in both main directions of the blade, i.e. flapwise and lead-lag. These tests are time consuming and rather expensive due to a high number of required load cycles, up to 5 million. Therefore, it is important t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A random, harmonic or custom input signal is selected according to project interest. The method is significantly less limited by specimen shape and is often suitable for full-scale in-situ welded product test [29].…”
Section: Introductionmentioning
confidence: 99%
“…A random, harmonic or custom input signal is selected according to project interest. The method is significantly less limited by specimen shape and is often suitable for full-scale in-situ welded product test [29].…”
Section: Introductionmentioning
confidence: 99%
“…A few papers have suggested optimization approaches to generate test setups that either maximize the accuracy level of the test loads respect to the target loads or minimize the total test time [19,20]. Lee and Park [19], for example, found an optimal flapwise test setup in which the exciter location was defined in a way that the actuating force and the maximum error between the test loads and the target loads were minimized in a 48.3-meters blade.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, Melcher et.al. [20] suggested an optimization scheme using virtual masses and spring elements to minimize the total test time, which can be applied to both uni-axial and bi-axial test setups. By applying this method, they found that 30% of the total test time was saved in comparison with current standard tests.…”
Section: Introductionmentioning
confidence: 99%